Prevalence of Campylobacter spp. in an adult population treated at Rawson Hospital in the City of Cordoba - Prieto, Carla Soledad; López, Ana Claudia; Paván, Javier; Littvik, Ana (Universidad Nacional de Córdoba. Facultad de Ciencias Médicas., 2021)
1 p.